Model simulations of air concentration and deposition of Cs137 from the Chernobyl accident 1986 - Langner, Joakim (SMHI - Swedish Meteorological and Hydrological Institute, 2019)
Model simulations of air concentration and deposition of Cs137 from the Chernobyl accident. Model results are available for the European domain at six hour time resolution and a geographical resolution of 50 km.

The files in this dataset correspond to part of the model results presented by Langner et al., Atmospheric Environment, 32, 4325-4333, 1998. Concentrations at ten model levels and accumulated dry, wet and total (wet+dry) deposition of Cs137 at one hour intervals for the time period 1986-04-25 19 UTC to 1986-05-10 12 UTC are stored in NetCDF-format. The model results correspond to the simulation using precipitation from KNMI. The units are Bq m-3 and kBq m-2 respectively. Coordinate information is given in the NetCDF files. The NetCDF files also include surface pressure, surface geopotential and model calculated boundary layer heights at six hour intervals. Further details about the model simulations can be found in Langner et al. (1998).

Modellsimuleringar av luftkoncentration och deponering av Cs137 från Tjernobylolyckan. Modellresultat finns tillgängliga för det europeiska området med sex timmars upplösning och en geografisk upplösning på 50 km.

Se engelska katalogsidan för mer detaljer: https://snd.gu.se/en/catalogue/study/ECDS0062
Modellsimuleringar av luftkoncentration och deposition av Cs137 från Tjernobylolyckan 1986 - Modellsimuleringar av luftkoncentration och deponering av Cs137 från Tjernobylolyckan 1986
Keywords: ATMOSPHERIC CHEMISTRY; TRACE ELEMENTS/TRACE METALS; AIR QUALITY; PARTICULATES; PLANETARY BOUNDARY LAYER HEIGHT; ATMOSPHERIC PRESSURE; deposition; deponering; pollutant concentration; koncentration av miljöföroreningar; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Environment; Miljö